Case Study : Shalicious Empire Sdn Bhd / Nur Syazwina Ab Rahim - Ab Rahim, Nur Syazwina (2021)
First thing first, this case study let us know about a very successful entrepreneur that has been chosen to be part of this case study. The chosen entrepreneur is Wan Siti Aishah Wan Hasan which her well-known name is Sha Hasan, the founder of Shalicious Empire and her husband name is Muhammad Hafiz. This case study will tell us about her successes and her ups and down in running the business over the years. From this case study, you will know about shalicious Empire background and also provide an explanation about the business description. All the things in this case study will be compile become a report for subject Fundementals of Entrepreneurship (ENT300) for our task for this semester. At the end of this case study, I realised that learning about entrepreneurship is important because to be a successful business person has a lot of step that need to follow. Moreover, Malaysia’s potential also depends on the country’s entrepreneurs as they hold shares and share with certain companies. To share with the readers, Sha Hasan are very workaholic, she never give up with her business, because of this, there are many people that make Sha Hasan as their idols in business. Last but not least, from this case study, Sha Hasan made me realised that having a disease did not mean you to stop doing something that you want. I am one of the Scoliosis fighter like Sha Hasan too, so by doing this case study, I feel more motivated to pursue my dreams because I know that pain is not a barrier for me to be a successful woman like Sha Hasan.